942 PERCUTANEOUS TREATMENT OF ACUTE PULMONARY EMBOLISM: A CASE REPORT. (15th December 2022) - Arturi, Federico; Fraccaro, Chiara; Napodano, Massimo; Masiero, Giulia; Fovino, Luca Nai; Fabris, Tommaso; Cardaioli, Francesco; Continisio, Saverio; Montonati, Carolina; Sciarretta, Tommaso; Zuccarelli, Vittorio; Simone, Tommaso; et al.
Abstract: Background: Pulmonary embolism (P.E.) is defined as an acute occlusion/subocclusion of pulmonary vascular vessels with a ranging clinical manifestation. A reperfusion therapy (preferably systemic thrombolysis) represents the first line therapy for high-risk patients. However, a percutaneous treatment option should be considered when thrombolysis is contraindicated or has failed. Case report: A 73 y.o. male, a former smoker with history of hypertension and dyslipidemia, was admitted for hemorrhagic stroke and was subsequently treated by neuro-surgical treatment. 7 days after admission, a cardiac arrest with pulseless electrical activity occurred but return of spontaneous circulation was rapidly achieved. For persistent hypotension vasopressor therapy was started. As first diagnostic work up, an EKG was performed showing sinus tachycardia and new onset of right bundle branch block; the echocardiography revealed a right ventricle dilatation with signs of pressure overload. At the computed tomography angiography of the pulmonary circulation, multiple and bilateral filling defects finally confirmed the diagnosis of acute high-risk P.E.. Given the absolute contraindication for thrombolysis and the good neurological prognosis, a catheter-directed therapy (CDT) was indicated by a multidisciplinary team evaluation. In the cath-lab, the angiography of pulmonary artery confirmed the presence of an occluding embolus in the left lower lobe artery and of a sub-occluding clot in the basal right lower lobe. Multiple aspirations were performed using a Flow Triever (Inari Medical, Irvine, CA) 20 Fr device advanced in the left and right pulmonary artery; a 16 Fr device, adopting child-in-mother technique, was also used, finally removing a large amount of thrombotic material (Fig.1). Restoration of the distal vascular segment perfusion was confirmed by a repeated angiography (Fig.2) and by the reduction of the invasive mean pulmonary artery pressure from 35 mmHg (pre-procedure) to 22 mmHg (post-procedure) (Fig.3). After the procedure, a rapid de-escalation of intravenous vasopressors was performed and the patient was transferred to the Intensive Care Unit, in stable conditions. Finally, the patient was discharged 7 days later, with the resolution of the EKG and echocardiography alterations. Conclusions: The Flow Triever device for the interventional treatment of P.E. is a CE approved aspiration system (3 sizes aspiration catheters) including 3 catheters with self-expanding nitinol for mechanical clot fragmentation. Evidence on the safety and efficacy of CDT is limited to observational single studies, a few small randomized trials and small single-arm cohort studies. Outcomes depend on the chosen technique, patient characteristics and local expertise. In particular, the FLARE study showed a significant Right/Left Ventricle ratio reduction after the use of a Flow Triever system while keeping a low rate of complications. The FLASH study is ongoing and the interim analysis showed encouraging results. However, randomized studies focusing on clinical outcomes and comparing CDT to conventional standard therapy (i.e. systemic thrombolysis for high-risk PE and anticoagulation for intermediate risk disease) are needed.